2023
DOI: 10.3390/v15091969
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Stochasticity as a Key Aspect of HIV-1 Latency

Alexia Damour,
Vera Slaninova,
Ovidiu Radulescu
et al.

Abstract: This review summarizes current advances in the role of transcriptional stochasticity in HIV-1 latency, which were possible in a large part due to the development of single-cell approaches. HIV-1 transcription proceeds in bursts of RNA production, which stem from the stochastic switching of the viral promoter between ON and OFF states. This switching is caused by random binding dynamics of transcription factors and nucleosomes to the viral promoter and occurs at several time scales from minutes to hours. Transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…However, advancement of modeling and analysis tools has revealed that the simple two-state model and associated parameters may not sufficiently recapitulate the complex relationship between these features. As such, more complex models incorporating some of these features such as RNAPII pausing and chromatin have been devised (reviewed in [ 124 ]). A common outcome of all these complex models is the realization that the HIV-1 transcriptional program is fragile and that perturbations at any of its regulatory phases: basal, host, and/or viral ( Figure 4 ) alters the magnitude of latent HIV-1 exit from latency, likely contributing to spontaneous reactivation (viral blips) [ 80 , 92 , 98 , 106 , 109 , 121 , 125 , 126 , 127 ].…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, advancement of modeling and analysis tools has revealed that the simple two-state model and associated parameters may not sufficiently recapitulate the complex relationship between these features. As such, more complex models incorporating some of these features such as RNAPII pausing and chromatin have been devised (reviewed in [ 124 ]). A common outcome of all these complex models is the realization that the HIV-1 transcriptional program is fragile and that perturbations at any of its regulatory phases: basal, host, and/or viral ( Figure 4 ) alters the magnitude of latent HIV-1 exit from latency, likely contributing to spontaneous reactivation (viral blips) [ 80 , 92 , 98 , 106 , 109 , 121 , 125 , 126 , 127 ].…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…An outstanding question of several landmarks discoveries in the field, including the topic of stochasticity [ 124 ], is what selective pressures shaped the viral genome to be regulated in such a manner and what are the evolutionary advantages. This is extremely important, given that two distinct patterns of gene activation (synchronous and stochastic) have been proposed to regulate gene expression in Drosophila [ 130 ] and mammals (reviewed in [ 97 ]).…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…One important consequence of the promoter-proximal pausing at the HIV-1 LTR is that HIV transcription at the level of an individual provirus occurs in rapid bursts [309,310]. The stochastic switching of the viral promoter between ON and OFF states is caused by random binding dynamics of the core transcription factors TBP, Sp1, and NF-κB, which can lead to intermittent clearance of the paused RNAP II complexes [311].…”
Section: Stochastic Transcription From the Viral Ltrmentioning
confidence: 99%